Dendritic mesoporous carbon nanoparticles for ultrahigh and fast adsorption of anthracene. (January 2019) - Kalantari, Mohammad; Zhang, Jun; Liu, Yang; Yu, Chengzhong
Abstract: Developing highly effective adsorbents for efficient decontamination of organic pollutants from water is an evasive aim for community well-being and environmental protection. Here, we report the successful fabrication of dendritic mesoporous carbon nanoparticles (DMCNs) as an advantageous adsorbent for ultrahigh and fast adsorption of anthracene. Dendritic mesoporous organosilica nanoparticles with an octadecyl-rich framework were utilized to synthesize DMCNs through carbonization and removal of silica. The DMCNs show a high carbon content, large mesopore volume of 1.484 cm 3 g −1 and high surface area of 1218 m 2 g −1 . It is revealed that both the high carbon content and highly accessible large surface area contribute to the excellent adsorption capacity towards anthracene (947.9 mg g −1 ), which is significantly higher than those in previous reports. Furthermore, the large radial pores of DMCNs with bimodal pore size distributions (2.1 and 18.4 nm) and open pore channels allow fast adsorption kinetics. The developed materials hold promise as effective adsorbents for efficient remediation of organic pollutants. Graphical abstract: Highlights: Dendritic mesoporous carbon nanoparticles with the designed structure. Outstanding elimination of anthracene: ultrahigh adsorption capacity and fast adsorption rate. High carbon content, highly accessible large surface area and large radial pores are responsible for this performance.